PENILAIAN PARAMETER ECOFISHINGPORT PADA PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - Retno Muninggar; Ernani Lubis; Budhi Hascaryo Iskandar (Jurnal Teknologi Perikanan dan Kelautan, 2020)
Nizam Zachman Oceanic Fishing Port of Jakarta (PPSNZJ) is the largest fishing port in Indonesia, as the center of industry and fishery product exports. On the other hand, PPSNZJ has various environmental problems such as water quality degradation and waste handling. The problem solved by the ecofishingport parameter approach (environmentally friendly port). The objective of the research is to assess the existing conditions of the PPSNZJ based on the ecofishingport parameters by determining the ecofishingport index. The research was carried out from January to March 2017. The data collection used a purposive and accidental sampling method. Data analysis using standard ecofishingport parameters which consisting of the physical environment aspects, socio-economy, fisheries catch, institutional and monitoring. The results showed that score was 0,63 for the environmental aspect, 0,27 for the socio-economic aspect, 0,40 for the fisheries catch aspect, and 0,50 for the institutional and monioring aspect. The analysis of ecofishingport index showed that PPSNZJ obtained an index value of 1.77 (toward ecofishingport).